2015
DOI: 10.1111/cmi.12476
|View full text |Cite
|
Sign up to set email alerts
|

Low-oxygen tensions found inSalmonella-infected gut tissue boostSalmonellareplication in macrophages by impairing antimicrobial activity and augmentingSalmonellavirulence

Abstract: In Salmonella infection, the Salmonella pathogenicity island-2 (SPI-2)-encoded type three secretion system (T3SS2) is of key importance for systemic disease and survival in host cells. For instance, in the streptomycin-pretreated mouse model SPI-2-dependent Salmonella replication in lamina propria CD11c(-)CXCR1(-) monocytic phagocytes/macrophages (MΦ) is required for the development of colitis. In addition, containment of intracellular Salmonella in the gut critically depends on the antimicrobial effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 69 publications
1
44
0
Order By: Relevance
“…Mucosa-associated microbiota are likely also prominent modulators of potential hypoxia-elicited autophagic responses (see Figure 2). Both commensal and pathogenic species have been shown to influence mucosal pO 2 and/or enterocyte HIF signaling (95,121,122), and ablation of epithelial HIF-1 increases susceptibility to pathogen infection in a number of studies (95,121). Reciprocally, intestinal oxygenation directly shapes the composition of gut microbial communities, and oxidative changes in intestinal inflammation may underlie the dysbiosis characteristic of IBD (5).…”
Section: Metabolic Regulation Of Epithelial Autophagymentioning
confidence: 99%
“…Mucosa-associated microbiota are likely also prominent modulators of potential hypoxia-elicited autophagic responses (see Figure 2). Both commensal and pathogenic species have been shown to influence mucosal pO 2 and/or enterocyte HIF signaling (95,121,122), and ablation of epithelial HIF-1 increases susceptibility to pathogen infection in a number of studies (95,121). Reciprocally, intestinal oxygenation directly shapes the composition of gut microbial communities, and oxidative changes in intestinal inflammation may underlie the dysbiosis characteristic of IBD (5).…”
Section: Metabolic Regulation Of Epithelial Autophagymentioning
confidence: 99%
“…For instance, a recent study demonstrated a significant reduction in gut tissue oxygen levels in mice infected orally with Salmonella . 68 Higher blood flow and hemoglobulin within the luminal environment in an inflamed intestine is thought to result in a more aerobic microenvironment in the lumen that favors the bloom of facultative anaerobes such as Enterobacteriaceae. 59 However, it remains challenging to measure luminal oxygen levels.…”
Section: Introductionmentioning
confidence: 99%
“…They also reflect an adaptive mechanism used by Salmonella to favor its infectivity in the gut lumen and tissues, where oxygen is rare and iron available to the bacterium (Kortman, Raffatellu, Swinkels, & Tjalsma, ; Jennewein et al . , ).…”
Section: Discussionmentioning
confidence: 97%
“…, ; Jennewein et al . , ). In contrast, iron is present in sufficient amounts to sustain bacterial replication in the gut, although the production of siderophores by enteric pathogens suggests a limited availability (Kortman et al .…”
Section: Discussionmentioning
confidence: 97%